Correlates of consulting health professionals for mental health in Canada and United States - Shaikh, Masood Ali; Shaikh, Irshad Ali (Journal of Ayub Medical College Abbottabad, 2005)
Over 15 percent of disease burden in established market economies like United States is caused by mental illness1. We describe age, gender, income and marital status associated with consulting a health professional for ones emotional or mental health in 18-85 year olds, and its prevalence in Canada and United States (USA). Using data from the Joint Canada/ United States Survey of Health, 2002-03 (JCUSH) 2, we selected all the respondents who had consulted a health professional about their emotional or mental health in the past twelve months. A stratified random digit dialing sampling design was adopted for JCUSH. Using SUDAAN 8.02, Odds ratios were calculated using multiple logistic regression method. Prevalence of consulting health professional for ones mental health was 10.09% in Canadians (n = 3505), and 10.54% in Americans (n = 5183). Compared to single/never-married individuals, widowed/separated/divorced individuals were more likely to have consulted in Canada (OR 1.94, 95% CI 1.32-2.83) and in USA (OR 1.44, 95% CI 1.05-1.97). While no statistically significant association was observed with being married. Compared to males, females were more likely to have had such consultations in Canada (OR 1.88, 95% CI 1.44-2.45), and USA (OR 2.11, 95% CI 1.70-2.63). Compared to 65-85 year olds, 18-44 year olds were more likely to have consulted in Canada (OR 2.87, 95% CI 1.91-4.33) and in USA (OR 2.14, 95% CI 1.55-2.95); as well as 45-64 year olds in Canada (OR 3.01, 95% CI 2.02-4.48) and in USA (OR 2.43, 95% CI 1.78-3.32). Income was assessed in three quintiles as household income adjusted for family size. Compared to upper middle and highest income quintile, individuals in lowest and lower middle income quintile were bestowed protection from such consultation in Canada (OR 0.71, 95% CI 0.51-0.97): while no statistically significant association was found with the middle income quintile. No statistically significant association was found with income and consultation in the USA. We conclude that widowed/separated/divorced women under the age of 65 were more likely to seek consultation for emotional or mental health problems, both in United States and Canada.